2010
DOI: 10.1007/s11145-010-9265-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of alphabetic knowledge in writing: connections to letter and word identification skills in preschool and kindergarten

Abstract: The writing skills of 286 children (157 female and 129 male) were studied by comparing name writing and letter writing scores from preschool to kindergarten with letter and word reading scores over the same time period. Two rubrics for scoring writing were compared to determine if scores based on multiple components (i.e., letter formation, orientation on the vertical axis, left-right orientation, and correct letter sequencing) would better reflect differences in children's writing knowledge in preschool and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…Children were first asked to copy three symbols (using a normal pencil) in an untimed task, and then 23 further letters were presented and children had a 1-min time limit to copy as many letters as possible. These letters were then scored using a qualitative judgment of form and vertical orientation, as has been used in the evaluation of handwriting (see Molfese et al, 2011). Up to 8 points were awarded for form and 3 points for vertical orientation, giving a maximum possible score of 11 points.…”
Section: Grapho-motor Skillsmentioning
confidence: 99%
“…Children were first asked to copy three symbols (using a normal pencil) in an untimed task, and then 23 further letters were presented and children had a 1-min time limit to copy as many letters as possible. These letters were then scored using a qualitative judgment of form and vertical orientation, as has been used in the evaluation of handwriting (see Molfese et al, 2011). Up to 8 points were awarded for form and 3 points for vertical orientation, giving a maximum possible score of 11 points.…”
Section: Grapho-motor Skillsmentioning
confidence: 99%
“…Children's writing has been identified as one of six key predictors of later reading with consistent, moderate effects (National Early Literacy Panel [NELP], 2008). Although only a small body of work focuses on the study of writing development, this work has identified young children's writing ability to predict other literacy skills including decoding (Bloodgood, 1999;Molfese et al, 2011), phonological awareness (Blair & Savage, 2006), and letter knowledge suggesting that writing may be a vital process for developing these other essential early literacy skills. Because writing skills do not develop naturally and children vary greatly in their writing skills at kindergarten entry (Welsch, Sullivan, & Justice, 2003), the ways in which early childhood educators support writing in the classroom appear to be important for understanding how children develop writing skills.…”
Section: Introductionmentioning
confidence: 99%
“…Although teaching children to categorize letters (instances of an ‘A’ belong to the named category ‘A’) is usually through sight and sound (seeing the letter, hearing its name, and hearing the sound it makes), growing research supports the idea that handwriting practice facilitates early letter categorization ability in the short term (Longcamp, Zerbato-Poudou, & Velay, 2005; James, 2010; Molfese et al, 2011) and supports various academic achievements later (Cahill, 2009; Graham, Harris, & Fink, 2000; Grissmer, Grimm, Aiyer, Murrah, & Steele, 2010; Harvey & Henderson, 1997; Simner, 1982, 1983). Nonetheless, by some accounts, preschool children spend only one minute of their school day in handwriting practice (Pelatti, Piasta, Justice, & O’Connell, 2014).…”
mentioning
confidence: 99%